Eksistensi Realisme dalam Aneksasi Israel Terhadap Palestina - Ida Susilowati; Muhammad Fauzi; Sepana Virqiyan; Azzam El Zahidin (JOURNAL of LEGAL RESEARCH, 2022)
The Palestinian people have fought for decades for their independence. However, the Palestinian area is being steadily reduced as a result of Israel's annexation efforts, therefore independence is not achieved. Political liberalism in the age of globalization is mostly ineffective, as international norms and regulations are unable to prevent Israel's annexation of Palestine. This study intends to investigate if international political realism still exists in the period of globalization, which is characterized by global political interdependence. In this work, a descriptive analytic approach with qualitative research and literature review approaches are utilized to collect data. The results demonstrate that the existence of realism may be demonstrated in the question of Israel's annexation of Palestine, where the use of force is still emphasized in order to further Israel's national interests. Israel continues to develop weapons technology in order to maintain control over Palestine as part of its annexation of the territory. In addition, Israel's alliance with Western nations, particularly the United States, and its noncompliance with international norms and laws demonstrate that political liberalism in the form of international organizations cannot be a solution to the Israeli occupation conflict in Palestine and a manifestation of realism in the age of globalization.